Bio-efficacy of argemonemexicana leaf extract fractions against tobacco caterpillar, spodopteraitura - KAVITHA.G,; GOKULAKRISHNAN.J,; BARANITHARAN.M, (International Journal of Pharma and Bio Sciences, 2019)
Man suffers extensively as a result of insect population in agriculture and health. In agriculture, insects have a direct effect on the growing part of the crop and causes severe harm leading to revenue loss. Tobaccocaterpillar and Spodopteralitura is a pest of soybean and being a polyphagousin nature, it attacks many crops. It sometimes occurs in epidemic form on soybean and causes losses to a greater extent. Control of insect pests uses synthetic chemicals that are more toxic and imperils health of farm operators, animals and food consumers. This negative effects on human health lead to a revival of attention in botanical insecticides due to their minimal costs and ecological side effects. Botanical insecticides are environmentally safer option of chemical insecticides and sometimes show promising results. Present investigation is aimed at pesticidal study of antifeedant, larvicidal, and ovicidalactivity. The antifeedant activity of methanol fractions in five different concentrations results 100% mortality up to 25, 50, 75, 100, 125 ppm against S. litura. The larvicidal activity of different fractions of methonol extracts was determined against S. litura at 20, 40, 60, 80, 100 ppm. Ovicidal activity (10, 20, 30, 40, 50ppm) on S. litura was maintained in the laboratory. The antifeedant activity calculated over 24hrs of mortality range observed in the neonate larvae, it significantly increased if the concentration increased from the range of 75-125 ppm. The results of 100 % mortality found later for the three different concentrations (75-125 ppm) of deterrent feeding. Fraction 4 showed the highest LC50 and LC90 values and are 25.80 and 68.45 ppm respectively on S. litura. Furthermore, there were no eggs hatchability recorded above 20, 30, 40 and 50ppm (100% mortality). We hypothesized that methanol fraction 4 was the main constituent responsible for the pesticidal activity of A. mexicana fractions.